Unveiling the Role of Ecto-5′-Nucleotidase/CD73 in Astrocyte Migration by Using Pharmacological Tools - Adzic, Marija; Nedeljkovic, Nadezda (Frontiers in Pharmacology, 2018)
CD73 is a bifunctional glycosylphosphatidylinositol (GPI)-anchored membrane protein which functions as ecto-5′-nucleotidase and a membrane receptor for extracellular matrix protein (ECM). A large body of evidence demonstrates a critical involvement of altered purine metabolism and particularly, increased expression of CD73 in a number of human disorders, including cancer and immunodeficiency. Massive up-regulation of CD73 was also found in reactive astrocytes in several experimental models of human neuropathologies. In all the pathological contexts studied so far, the increased expression of CD73 has been associated with the altered ability of cells to adhere and/or migrate. Thus, we hypothesized that increased expression of CD73 in reactive astrocytes has a role in the process of astrocyte adhesion and migration. In the present study, the involvement of CD73 in astrocyte migration was investigated in the scratch wound assay (SW), using primary astrocyte culture prepared from neonatal rat cortex. The cultures were treated with one of the following pharmacological inhibitors which preferentially target individual functions of CD73: a) α,β-methylene ADP (APCP), which inhibits the catalytic activity of CD73 b) polyclonal anti-CD73 antibodies, which bind to the internal epitope of CD73 molecule and mask their surface exposure and c) small interfering CD73-RNA (siCD73), which silences the expression of CD73 gene. It was concluded that approaches that reduce surface expression of CD73 increase migration velocity and promote wound closure in the scratch wound assay, while inhibition of the enzyme activity by APCP induces redistribution of CD73 molecules at the cell surface, thus indirectly affecting cell adhesion and migration. Application of anti-CD73 antibodies induces a decrease in CD73 activity and membrane expression, through CD73 molecules shedding and their release to the culture media. In addition, all applied pharmacological inhibitors differentially affect other aspects of astrocyte function in vitro, including reduced cell proliferation, altered expression of adenosine receptors and increased expression of ERK1/2. Altogether these data imply that CD73 participates in cell adhesion/migration and transmits extracellular signals through interactions with ECM.